Sesamum Indicum Gel: A Natural Foe to Candida Albicans - Keerthana Selvam; Suman J. Lakshmi; Senthil Kumar Balasubramanian (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Oral candidiasis is a common fungal infection typically treated with antifungal drugs, which may cause side effects. Herbal treatments have emerged as a potential natural alternative with fewer adverse effects. Objective: This exploratory study aimed to evaluate the antifungal potential of a gel formulated using the most effective extract of Sesamum indicum root. Objectives included identifying the effective solvent, assessing antifungal activity via the well diffusion method, analyzing active compounds through GC-MS, and evaluating the antifungal activity of the formulated gel. Methods: Root extracts were prepared by macerating Sesamum indicum powder in ethanol, water, and hexane. Different amounts of root powder (10, 15, 20, and 25 grams) were mixed with 100 mL of ethanol to determine the most effective concentration. The extract showing the highest antifungal activity was analyzed using GC-MS to identify bioactive compounds. A gel was then formulated and tested in vitro for antifungal efficacy. Due to the exploratory nature of the study, a limited sample size was used to generate preliminary findings. Results: The ethanol extract exhibited the highest antifungal activity. GC-MS identified key compounds including (S)-(+)-2-Amino-3-methyl-1-butanol, 1,3-Propanediol, 2-(hydroxymethyl)-2-nitro, and 2,4-Di-tert-butyl-phenol. The herbal gel showed a 10.03 mm zone of inhibition, compared to 11.25 mm for clotrimazole, with statistically significant results. Conclusion: The formulated herbal gel demonstrated promising antifungal activity comparable to clotrimazole. However, the small sample size and preliminary nature of this study warrant further research to confirm efficacy, safety, and clinical applicability.